Obstacles to Creative Citizenship - Miller James (Cultural Science)
The Creative Citizens project asks whether new media enhance new forms and scale of creative civic activities. If so, the project seeks to identify practices that will exploit this new individual and collective activity, presumably as a means of achieving authentic self-governance. This paper considers three potential obstacles to the realization of a creative citizenship: that the sort of political engagement it fosters may be too personal and episodic; that the commonsensical political knowledge typical of politics known at a distance as performance and simulation may impose further limits on effective understanding and engagement; and that the emerging new media environment may be different enough that today’s digital skills and relationships may be insufficient in the medium term. The paper looks at the same conditions that inspire the creative citizenship project and reaches reverse conclusions – but not on the grounds of nostalgia or pessimism.